The Education Characters Using Local Wisdom Approach - Sari, Dian Cita; Isnaini, Lailatul (International Journal of Applied Guidance and Counseling, 2021)
Character education in New Normal Era based on a local wisdom approach is a solution to managing  education polemic that has been affected by  Covid-19 pandemic. One of  local wisdom approaches is through  G12 (Gurindam Dua Belas) approach which is  local wisdom of ethnic Malays as well as didactic literary works.  classification of  G12 document is used as an effort to strengn  character of  nation. Various problems of  character of  nation's children in  New Normal era such as moral decadence, sexual disorders, acts of plagiarism, excessive love for social media in  younger generation have become a moral crisis that disturbs  world of education, family and society, so re is a need for value development. To organize values, Gurindam Dua Belas is a solution that is implemented through habituation and exemplary. This research method is a descriptive method with a qualitative approach,  researcher collects primary sources and secondary sources related to  discussion, analyzes  contents of G12 and  results of G12 consist of 12 articles, containing  values of Islamic teachings, especially values.  purpose of this study is to describe  values that exist in Gurindam 12.  results obtained include: a) making an effort to introduce and foster local ethnic Malay wisdom, b) to describe  character education of Gurindam 12 and  values in it, se values include: not lying, prohibition of cursing and criticizing, gentle hands, patient, gentle, sincere, guarding heart, love to give, thrifty, polite, trustworthy, diligent, obedient to  mor and far and study hard. c) Growing and fostering  values of Gurindam 12 in students.  conclusion of this study is that  values of G12 need to be actualized continuously by  community and  young generation in all ir life activities in order to become individuals with Gurindam 12 characteristics.